Sex-specific decision-making impairments and striatal dopaminergic changes after binge drinking history in rats - Sauton, Pierre; Jeanblanc, Jerome; Benzerouk, Farid; Gierski, Fabien; Naassila, Mickael (Frontiers in Pharmacology, 2023)
Binge drinking (BD) is a harmful behavior for health and is a predictive factor for the development of alcohol addiction. Weak decision-making (DM) capacities could play a role in the vulnerability to BD which in turn would lead to DM impairments, thus perpetuating BD. Longitudinal preclinical studies are however lacking and necessary to understand this complex relationship. Both DM and BD are influenced by sex and involve dopamine release in the core of the nucleus accumbens, a central mechanism regulated by dopamine D2/3 autoreceptors. In this context, we used an operant self-administration procedure of BD in male and female rats, and longitudinally assessed DM capacity, memory and anxiety-like behavior. To better understand the mechanisms potentially involved in the relationship between DM and BD, ex vivo dopamine transmission was assessed short term after the end of the binge exposure in the core of the nucleus accumbens (NAc) using the fast-scan cyclic voltammetry (FSCV) technique and the D2/3 agonist quinpirole. We found important basal sex differences in DM, with female rats showing better performances at baseline. Choice processes were impaired exclusively in males after BD history, associated with a decrease in impulse control in both sexes, while memory and anxiety-like behavior were not affected. Our neurobiological results demonstrate that BD did not affect basal dopamine signaling in the NAc core, regardless of the sex, but reveal changes in the sensitivity to the inhibitory effects of quinpirole in females. DM impairments were neither associated with changes in basal dopamine signaling nor pre-synaptic D2 activity. Overall, our findings show that BD affects both DM processes and dopamine transmission in the core of the NAc in a sex-related manner, further suggesting that these effects may play a role in the vicious cycle leading to BD perpetuation and the early onset of AUD. Our results may inform novel strategies for therapeutic and prevention interventions.